Novel opioid-neurotensin-based hybrid peptide with spinal long-lasting antinociceptive activity and a propensity to delay tolerance development - Karolina Frączek; Mattia Ferraiolo; Emmanuel Hermans; Magdalena Bujalska-Zadrozny; Kaja Kasarello; Anna Erdei; Kamila Kulik; Agnieszka Kowalczyk; Piotr Wojciechowski; Dorota Sulejczak; Piotr Sosnowski; Sebastian Granica; et al. (Elsevier, 2020)
The behavioral responses exerted by spinal administration of the opioid-neurotensin hybrid peptide, PK23, were studied in adult male rats. The antinociceptive effect upon exposure to a thermal stimulus, as well as tolerance development, was assessed in an acute pain model. The PK23 chimera at a dose of 10 nmol/rat produced a potent pain-relieving effect, especially after its intrathecal administration. Compared with intrathecal morphine, this novel compound was found to possess a favourable side effect profile characterized by a reduced scratch reflex, delayed development of analgesic tolerance or an absence of motor impairments when given in the same manner, though some animals died following barrel rotation as a result of its i.c.v. administration (in particular at doses higher than 10 nmol/rat). Nonetheless, these results suggest the potential use of hybrid compounds encompassing both opioid and neurotensin structural fragments in pain management. This highlights the enormous potential of synthetic neurotensin analogues as promising future analgesics.